Robert Louis Stevenson's Pacific Impressions Photography and Travel Writing, 1888-1894 - Manfredi, Carla (Palgrave Studies in Nineteenth-Century Writing and Culture, 2018)
This book tackles photography's role during Robert Louis Stevenson's travels throughout the Pacific Island region and is the first study of his family's previously unpublished photographs. Cutting across disciplinary boundaries, the book integrates photographs with letters, non-fiction, and poetry, and includes much unpublished material. The original readings of photographs and non-fiction highlight Stevenson's engagement with colonial ideology and reality and advance new arguments about Victorian travel, settlement, and colonialisms in the Pacific. Like the Stevensons, the book moves from the Marquesas to the atolls of the Gilbert Islands in Micronesia; from the Kingdom of Hawai'i's political ambitions to Samoan plantations and the Stevensons' settlement at Vailima. Central to this study is the notion that Pacific history and Pacific Island cultures matter to the interpretation of Stevenson's work, and a rigorous historical and cultural contextualization ensures that local details structure literary and photographic interpretation. The book's historical grounding is key to its insightful conclusions regarding travel, settlement, photography, and colonialism.